Chronometers and chronometry on British Voyages of Exploration, 1819-1836 - Akkermans, Emily Jane (The University of Edinburgh, 2021)
This thesis demonstrates how a historical geography of the chronometer can inform our understanding of the production and circulation of scientific knowledge at sea. The history and development of the marine chronometer has been a topic of considerable research. Yet few studies have focused on their actual use at sea, particularly during the first half of the nineteenth century. This thesis aims to understand how officers, charged with the use and care of chronometers at sea, took up the use of these instruments and developed practices for the purpose of determining longitude at sea that would later become widespread. The thesis draws upon work in the history and historical geography of science and the history of technology and of navigational instruments to provide the context to its detailed empirical content. The thesis examines the use of chronometers on Royal Navy vessels by considering four detailed case studies of voyages and navigational practice between 1819 and 1836. These are William Edward Parry’s three attempts to find a North-West Passage; William Owen’s survey of the east coast of Africa, Henry Foster’s scientific expedition in the Atlantic and Robert Fitzroy’s survey of South America and circumnavigation. The research presents a detailed analysis of a broad range of archival material, including navigational notebooks, chronometric data books, journals, correspondence, published travel narratives and navigational manuals. The thesis pays attention to the social and institutional networks in which the users of these instruments operated, including a consideration of the role of the State, the Royal Society and the Admiralty. It considers how reforms within the Royal Navy during this period shaped the role of naval officers, who turned to scientific pursuits to further their naval careers and to their close associations with scientific societies. The thesis argues that we should not consider ‘longitude by chronometer’ as a single instrumental measurement easily vi achieved, but, rather as a complex ...